RESPON PETANI DI PERKEBUNAN DESA MAKARTI JAYA POHUWATO TERHADAP SERANGAN Macaca hecki - R. Juramang, Risnayanti; Faqih, Ahmad; K. Toiyo, Frandika (Universitas Cokroaminoto Palopo, 2024)
This research aims to determine the response of farmers in the Makarti Jaya Pohuwato Village plantation to the Macaca hecki attack. The number of respondents found at the research location was 20 people. Analysis of the research results was carried out using the interview method and analyzed using a Likert scale. People (farmers) found on plantation land were interviewed using a questionnaire. The Likert scale can measure individual behavior using several questions by providing responses of strongly agree, agree, between agree and disagree (neutral) and strongly disagree. The community's response to the presence of Macaca hecki in the plantation area received a score of 88% (Strongly Agree) that its existence Macaca hecki in plantation areas is very disturbing, and received a score of 77% (Agree) that there is a possibility of increasing crop yields if the disturbance from Macaca hecki is reduced.